Masculinity as an Alternative Parameter of Ethnic Identity: Montenegrins in the Village of Lovćenac - Saša Nedeljković (Etnoantropološki Problemi, 2010)
The village of Lovćenac is located in the region of Bačka, practically halfway between the cities of Novi Sad and Subotica, and has a population of about 4,000. After World War II it was settled by Montenegrins from the region known as "Old Montenegro". Today, the residents of Lovćenac are faced with great challenges of ethnic and national identification. The village is a stronghold of Montenegrin nationalist feeling in Serbia, and the only place where Montenegrin "traditional" culture has been preserved to this day. Having studied Montenegrins in Serbian towns and cities, my intention was to study the identity formula of a rural Montenegrin community in Serbia, and it was with this aim that in 2009 I conducted a study of Lovćenac villagers' identity, using observation and the interview as methodological tools. I paid particular attention to the study of alternative parameters of ethnic identity, specifically the phenomenon of masculinity, which in this case could provide an important analytical instrument. In this particular case, masculinity is manifested through specific and adapted forms of aggresivity, heterosexuality, authoritarianism, laziness etc. These syndroms and concepts are important for self-determination, but also for description, making ethnic boundaries sharper and more distinct. This concept has proved to be especially useful in the case of identification with smaller ethnic (clan) and regional groups, i.e. in intragroup classification. Masculinity has turned out to be an important regulator of interethnic and intraethnic relations, that is, a relational category that is invoked and used when descent, regional affiliation, religion and language are insufficiently clear criteria for ethnic systematization and operationalization.